Orthologous Revelation between Elaeis guineensis, Arabidopsis thaliana and Solanum lycopersicum - Samsulrizal, Nurul Hidayah; Hazuki, Muhammad Daniel; Ahmad Azmi, Nur Sabrina; Mat Said, Zatty Syamimi Adura; Abdul Wahab, Nurniwalis; Ramli, Zubaidah (International Society of Academicians, 2020)
Oil palm is an important commodity crop in Malaysia as major contributor to agriculture sector. Thus, the need for better yield production is urgent to accommodate rising local and global demand while reducing the land expansion for oil palm plantation. This can be achieved by identifying the agronomical important traits in oil palm using comparative genomic approach. In this study, gene related to plant height, fruit development and fruit ripening in oil palm were predicted by comparing Elaeis guineensis genome sequence with Arabidopsis thaliana and Solanum lycopersicum genome sequence. The model plant chosen are based on its special attribute such as completely sequenced and fleshy fruit model. The analysis begun with orthology analysis using InParanoid, and SonicParanoid. There are 9,624 orthologous genes identified common among species selected. The reformatted orthologous genes were then annotated with Gene Ontology (GO) using Blast2GO program. The process of annotation includes blast with local database (DIAMOND), mapping, annotation and project statistical analysis. 100% of the orthologous gene has sequence of significant similarity but only 61.79% of the sequence has GO assignment. By using the annotated orthologous genes generated, only small amount of gene associated with trait of interest was predicted i.e. gibberellins (GAs) 10 genes, bassinosteroids (BRs) 14 genes, auxin (9 genes), fruit development (8 genes) and fruit ripeing (4 genes). These agronomical important genes could be utilized in genetic engineering and molecular breeding to improve the production of palm oils.